A Rare Tumor of Breast - Diffuse B-Cell Lymphoma - Shruthi Kamal Venkataraman; Sivarahini Ganesan; Ann Kurian (Dr. Annil Mahajan, 2024)
Primary breast lymphoma (PBL) is considered a rare clinical entity forming about 0.4%-0.5% of all breast tumors and forming about 1.7%-2.2% of extra nodal NHL. Here we report a case of postmenopausal women presenting with a breast lump turned out to be a Diffuse B-cell Lymphoma of breast.